2004
DOI: 10.22621/cfn.v118i2.914
|View full text |Cite
|
Sign up to set email alerts
|

Spring Dispersal Patterns of Red-winged Blackbirds, <em>Agelaius phoeniceus</em>, Staging in Eastern South Dakota

Abstract: Red-winged Blackbirds (Agelaius phoeniceus) are very abundant summer residents throughout the Prairie Pothole Region of central North America. In late summer they assemble in post-breeding flocks that cause significant amounts of agricultural damage, particularly in sunflower fields near natal sites. In April 2001, we aerially color-marked ~370,000 Red-winged Blackbirds near Badger, South Dakota (44°48'N, 97°21'W), to determine if migrants staging here were summer residents in sunflower production areas ~350 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Long-distance migration is stressful on birds, often leading to decreased immune function resulting in enhanced susceptibility to disease (45). As avian wildlife migrate, they make a series of flights interrupted with many stopovers (29). Stopover locations characteristically have dense congregations of birds, which can potentially facilitate pathogen transfer (15,43).…”
mentioning
confidence: 99%
“…Long-distance migration is stressful on birds, often leading to decreased immune function resulting in enhanced susceptibility to disease (45). As avian wildlife migrate, they make a series of flights interrupted with many stopovers (29). Stopover locations characteristically have dense congregations of birds, which can potentially facilitate pathogen transfer (15,43).…”
mentioning
confidence: 99%
“…In the mid-1990s, a multiyear assessment was conducted on the feasibility of an operational DRC-1339 program for reducing the number of spring-migrating blackbirds in eastern South Dakota , Homan et al 2004). This area is a major stopover site used by millions of blackbirds migrating toward their breeding territories in sunflower production areas approximately 350 km to the northwest , Homan et al 2004).…”
Section: Drc-1339 Baiting At Spring-migratory Roostsmentioning
confidence: 99%
“…This area is a major stopover site used by millions of blackbirds migrating toward their breeding territories in sunflower production areas approximately 350 km to the northwest , Homan et al 2004). Linz and colleagues (2003) demonstrated that thousands of blackbirds could be attracted to small field plots in cornfields during the spring.…”
Section: Drc-1339 Baiting At Spring-migratory Roostsmentioning
confidence: 99%
“…We used the DayGlo Fluorescent particle marker formulation described by Linz et al (1991), Knittle et al (1996), and Homan et al (2004). A 950 mL solution of this formulation was mixed within 30 min of application.…”
Section: Flight Pen Studymentioning
confidence: 99%
“…Knittle et al (1987) marked 10.6 million red-winged blackbirds (Agelaius phoeniceus) in Missouri and South Dakota, USA, with marker. Linz et al (1991) and Homan et al (2004) used a different marker formulation to mark 300 000 and 370 000 blackbirds in North Dakota and South Dakota, USA, respectively. After marking, birds in these studies were systematically shot and collected along migrational pathways or in breeding areas and examined for marker.…”
Section: Introductionmentioning
confidence: 99%